Analisis Kinerja Keuangan Bank Syariah dan Bank Konvensional di Indonesia - Prasetyo, Indra (Universitas Brawijaya, Indonesia, 2008)
The objective of this research are to compare performance of syariah banking performance which use profit and loss sharing system and conventional banking performance which use interest system by CAMEL approach that including valuation of capital aspect, asset quality aspect, management aspect, earning aspect, and liquidity aspect. Beside that, to identify the most distinguishable performance variable between syariah system and conventional system. Data exploited in this research is secondary data alike financial ratios on publication of bank's quarterly that ezposed on Indonesian Central Bank's website (htpp://www/bi/go/id). The result of this research show that performance of syariah banking and conventional banking have been better, sharia banking have reached the higher LDE, ROA ratio significantly otherwise conventional banking performance was better than CAR. Sharia banking performance was better than conventional banking performance based on LDR, and second was NPM.